Operational management of the bus fleet maintenance and repair system - E. V. Feklin (Вестник СибАДИ, 2022)
Introduction. Recently, due to the increase in the number of vehicles, including public transport, there is a need to streamline the system of maintenance and repair, taking into account the mass of incoming applications for these operations. A decrease in productivity may occur due to an unclear distribution of work by performers, inconsistency of their actions in time and irrational use of technological equipment. The purpose of the research is to develop a system for organizing maintenance and repair of rolling stock based on the principles of centralization and cooperation with other production structures. To achieve this goal, statistical methods, methods of the theory of random processes and queuing theory are used. The concentration of production occurs either due to the growth of the share of large enterprises in the total volume of production of the region / industry (transportation of passengers of the metropolis) or due to the growth of the size of the manufacturing enterprises themselves. The process of concentration can be argued from the standpoint of the principles of synergetics.Materials and methods. The article discusses the operational management of the system of maintenance and repair of the bus fleet. The division of tasks of the technical service of a motor transport enterprise into four complexes is presented. Two ways of drawing up a schedule are analyzed: calendar and by actual mileage of cars. The analysis revealed the advantages and disadvantages of each of the options. The advantages and disadvantages of universal and specialized posts are analyzed, indicating ways to eliminate the identified shortcomings. The positive effect of centralization of management of the specified complexes of tasks for maintenance and repair of rolling stock is substantiated.Results. A scheme for servicing applications for routine repairs with decentralized and centralized systems for managing the production of routine repairs of rolling stock is proposed. The basic principles of functioning of a centralized production management system are described. A general structural scheme of centralized specialized production is proposed. The structural composition of the pre-production complex is presented, with a description of each unit included in its system: a complete set group, an intermediate warehouse, a transport section, a washing and defect section, a tool section. The tasks of the operational management department and the information processing and analysis department, which are part of the control center of a centralized specialized production, are outlined.Discussion and conclusions. The results of the study are intended for the enterprises of passenger transport. This study is an integral part of the development of a common system of centralization and cooperation of maintenance of rolling stock.